Karyomorphological study of Enhydra fluctuans Lour. (Asteraceae) - Rahman, MS (Bangladesh Journal of Scientific and Industrial Research, 2019)
In the present study, karyomorphological features of Enhydra fluctuans Lour. were investigated. Orcein-staining was used for the authentic chromosomal characterization and identification. In E. fluctuans ‘Simple Chromocenter Type’ of interphase nuclei was observed with many small heterochromatin blocks after orcein staining. Prophase chromosomes showed ‘Gradient Type’ with orcein staining. This species was found to possess 2n=10x=110 with basic chromosome number x=11 and this is probably the first report for this species. The centromeric formula of this species was ‘38m+70sm+2ac’. The above features indicated that E. fluctuans is an advance polyploid with asymmetric karyotype. The total chromatin length (2n) was 295.92 μm. Individual chromosome length ranged from 1.84-4.26 μm. The relative length of each chromosome ranged from 0.006-0.014. The above mentioned data will be useful for karyomorphological characterization of E. fluctuans from Bangladesh. Bangladesh J. Sci. Ind. Res.54(4), 283-288, 2019